2015
DOI: 10.1039/c5cp02197a
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent interactions in ionic liquid ion pairs and ion pair dimers: a quantum chemical calculation analysis

Abstract: Ionic liquids (ILs) being composed of bulky multiatomic ions reveal a plethora of non-covalent interactions which determine their microscopic structure. In order to establish the main peculiarities of these interactions in an IL-environment, we have performed quantum chemical calculations for a set of representative model molecular clusters. These calculations were coupled with advanced methods of analysis of the electron density distribution, namely, the quantum theory of atoms in molecules (QTAIM) and the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 95 publications
(232 reference statements)
6
67
0
1
Order By: Relevance
“…However, as it has been recently highlighted by us for a set of neat C 4 mim + -based ILs and for mixtures with acetonitrile, [17][18] as well as for a similar set of ion pairs considered in simulations of neat…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as it has been recently highlighted by us for a set of neat C 4 mim + -based ILs and for mixtures with acetonitrile, [17][18] as well as for a similar set of ion pairs considered in simulations of neat…”
Section: Introductionmentioning
confidence: 99%
“…19 However, as we have shown later in this paper, the mentioned potential energy profile is strikingly different between ILs bearing Cl − anion and multiatomic anions with delocalized charge distribution, such as BF 4 − . 18 All these findings highlight the need for detailed and systematic studies of ILs by means of molecular simulations. Here the term 'detailed' refers to the atomic-level description of the local structure around particularly relevant interaction sites, whereas 'systematic' implies a thoughtful selection of systems to be studied so that the eventual conclusions could be of use for the subsequent design of novel better performing ILs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the approach employed, most research efforts are made on N, N‐dialkylimidazolium salts and focus primarily on interactions between anion and acidic protons of aromatic ring . The aliphatic C−H⋅⋅X (X= O, N, F etc.)…”
Section: Introductionmentioning
confidence: 99%
“…One involves the anion as the H‐bond acceptor and the C―H groups on the imidazolium ring as the H‐bond donors and is often referred to as aromatic or primary H‐bonds, while the other, known as aliphatic or secondary H‐bonds, is formed between the anion and C―H groups on the N ‐alkyl sidechains. While weaker, quantum theory of atoms in molecules (QTAIM) calculations have shown that the strengths of aliphatic C―H⋅⋅⋅X H‐bonds are in some cases comparable to those of their aromatic counterparts, suggesting that these interactions also play a central role in the ordering of the local structure of ILs . To date, however, there is virtually no experimental data that can corroborate these theoretical results.…”
Section: Introductionmentioning
confidence: 99%